High levels of serum TIMP-1 correlate with advanced disease and predict for poor survival in patients with multiple myeloma treated with novel agents - Terpos, E.; Dimopoulos, M.A.; Shrivastava, V.; Leitzel, K.; Christoulas, D.; Migkou, M.; Gavriatopoulou, M.; Anargyrou, K.; Hamer, P.; Kastritis, E.; Carney, W.; Lipton, A. (Leukemia Research, 2010)
Tissue inhibitor of metalloproteinase-1 (TIMP-1) was evaluated in the pre-treatment serum of 55 newly diagnosed patients with symptomatic myeloma. TIMP-1 was elevated in 47% of patients and correlated with lytic bone disease and increased bone resorption. Importantly, TIMP-1 correlated with ISS stage (p=0.005) and was an independent prognostic covariate for survival [HR: 1.003 (1-1.006), p=0.004] in these patients who were all treated with novel agents (bortezomib and/or IMiDs) during their disease course. Our study provides evidence that pre-treatment serum TIMP-1 is associated with advanced myeloma and suggests the further evaluation of this molecule to better determine its prognostic potential in MM. © 2009 Elsevier Ltd.
Keywords: Bone disease; bone markers; multiple myeloma; Survival; Tissue inhibitor of metalloproteinase-1 (TIMP-1)